Kinetics and Mechanism of Periodate Oxidation of p-Phenetidine - Kaushik, R.D.; Chaubey, A.K.; Garg, P.K (Asian Journal of Chemistry, 2010)
Kinetics of periodate oxidation of p-phenetidine in acetone-water medium has been investigated spectrophotometrically. Reaction has been found to be first order in each of the reactants. 4-Ethoxy- 1,2-benzoquinone has been separated and characterized as the main product. Rate law has been derived and suitable mechanism suggested based on the stoichiometry and thermodynamic parameters evaluated, the product identified and the effect of pH, dielectric constant, ionic strength and free radical scavengers on the reaction rate.